TINJAUAN HUKUM POSITIF DAN MAQOSID SYARIAH TERHADAP PEMBATALAN PERNIKAHAN KARENA SUAMI HOMOSEKSUAL DALAM PUTUSAN PENGADILAN AGAMA NOMOR 2395/Pdt.G/2024/PA.JT - Bafadal, Ahmad Anwar; Badri , Muhammad arifin (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study examines the annulment of marriage due to the concealment of sexual orientation by the husband, based on the decision of the East Jakarta Religious Court Number 2395/Pdt.G/2024/PA.JT. The main focus of this research is to assess the validity of the ruling from the perspective of Indonesian positive law and maqāṣid al-sharī‘ah. The research method employed is normative-juridical, using a case study approach, statutory analysis, and the framework of maqāṣid al-sharī‘ah. The contributions of this study include: strengthening the concept of victim protection through the fasakh mechanism as a just legal solution. The findings show that the husband's concealment of his sexual identity constitutes substantial fraud, thus fulfilling the legal grounds for annulment as stipulated in Article 27 of Law No. 1 of 1974 and Article 72 of the Compilation of Islamic Law (KHI). From the perspective of maqāṣid al-sharī‘ah, this condition violates the five fundamental principles (al-ḍarūriyyāt): ḥifẓ al-dīn (protection of religion), al-nafs (life), al-‘aql (intellect), al-nasl (lineage), and al-māl (wealth). The court's decision to grant the annulment is regarded as upholding substantive justice and the protection of women's dignity. The results of this research serve as a critical reference for judges, legal practitioners, and the public in understanding the complexities of marriage annulment caused by sexual deviation.